(untitled) (Journal of Environmental Microbiology and Toxicology, 2017)
Acetylcholinesterase (AChE) is frequently used as an inhibitive assay for insecticides. Relatively little is known about AChE inhibition properties on heavy metals. This present study assesses the potential of the AChE from the brain of Puntius schwanenfeldii, which forms as a waste from the aquaculture industry, as an inhibitive assay for heavy metals. The results of the study revealed that Ag+, Cu2+, and Hg2+ completely inhibited AChE activity during initial screening. Furthermore, when tested at various concentrations, the heavy metals demonstrated exponential decay type inhibition curves. The calculated IC50 for the heavy metals Ag+, Cu2+, and Hg2+ were observed to be 0.2498, 0.2427 and 0.2255 mg/L, respectively. The present assay for copper was comparable in sensitivity to assay methods such as immobilized urease, 15-min MicrotoxTM,48-h Daphnia magna, 96-h Rainbow trout, papain and bromelain assays while the present assay for mercury was significantly more sensitive than immobilized urease, equivalent in sensitivity to the rest of the assays, but less sensitive than the papain and bromelain assays. The present assay for silver was more sensitive to all of the assays with the exception of the rainbow trout assay. In conclusion, the findings in this study indicate that the assay, which can be carried out in less than 30 minutes at ambient temperature can be a useful assay for monitoring both insecticides and heavy metals pollution.